The concepts and laws applicable to hybrid threats, with a special focus on Europe - Susana Sanz-Caballero (Humanities & Social Sciences Communications, 2023)
Abstract In this paper, the consequences of the lack of definition of so-called hybrid threats is explored. Special attention was paid to the importance of the work already completed by the North Atlantic Treaty Organisation (NATO) and the European Union (EU) regarding the ever evolving types of actions associated with hybrid threats in the so called grey zone. The latter can be thought of as activities undertaken by one state that are harmful to another, albeit not legal acts of war, sometimes referred to as a malevolent manifestation of the concept of peace. The vastly different experiences of democratic and authoritarian states acting in the grey zone was also examined. In addition, the law applicable to hybrid threats was studied to determine if the legal framework is sufficiently adapted to repel state-sponsored and non-state-sponsored hybrid threats. In addition, the use of the European Convention on Human Rights in the struggle against hybrid threats in Europe and the limits to how state parties can react to hybrid threats established by this treaty was analysed. Lastly, the international rules of attribution of responsibility and difficulties associated with their application with respect to hybrid threats was considered. This article is structured in two parts. The first part explores the difficulty of defining hybrid threats, while the second presents the legal framework used to counter such threats, both at the international and European levels.